History Under Censorship: Józef Piłsudski’s Eastern Policy in Polish Marxist Historiography (1945–1989) - Vitalii Borymskyi (Acta Baltico-Slavica, 2023)
The article examines the historiography and history policy in the communist Polish People’s Republic (1945–1989) regarding the Eastern policy of Józef Piłsudski. Poland was one of the most important countries in the socialist camp, and it had a complicated history of relations with the USSR. Under Moscow’s influence, Poland had to adapt its official history to the Soviet one. This was especially difficult to accomplish considering recent hostile Polish-Soviet relations. Consequently, implementing such a history policy was a complex and uneven process. Piłsudski’s policy was treated extremely negatively during the Stalinist period, a view that softened in subsequent years under the influence of a gradual liberalisation of the history policy of the state. Although the general interpretation of Piłsudski’s Eastern policy remained negative until 1989, it became significantly different from Soviet dogmas. The source of this study were both propaganda texts, professional historiography and historical essays.